The Students’ Problem-Solving Abilities in Mathematics and English at the Secondary School Level - Jamal Asad Mezel; Nedhal Abdul Hafedh Taher (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This paper investigates the perspectives of secondary school teachers of both mathematics and English on students’ abilities in problem solving in both subjects. Thus, the following objectives are intended to be achieved: identifying the students’ skills in problem-solving in both mathematics and English; and are there significant differences in both English and mathematics teachers’ perspectives on students’ problem-solving skills according to school, stage, and gender? The quantitative, analytical, and descriptive methods used in the collection, classification, and processing of the study's data. The target population of the study was all secondary school math and English teachers in Erbil. A sample of 72 teachers—26 male and 46 female—were selected from seven secondary schools using a random sampling technique for the academic year 2023–2024. Two questionnaires, one with 14 items for math teachers and another with 13 items for English teachers, were used to collect the data. Teachers' responses were scored on a scale of 1 for strongly disagree, 2 for disagree, 3 for neutral, 4 for agree, and 5 for strongly agree. The questionnaire's reliability, validity, and consistency were examined. and the validity and reliability of the questionnaire were checked. SPSS was used, mean, standard deviation, correlation, and ANOVA were used to analyze the data. The study's findings confirmed similarities in problem-solving abilities that were shared between mathematics and English students, and there are no significant differences between the two areas due to the averages of students’ performance in problem-solving in both disciplines, which are fairly close to each other